Effectiveness of paracervical block for pain relief in women undergoing hysterosalpingography - Shikha Jain; Dattaprasad B Inamdar; Abha Majumdar; Deepak K Jain (Wolters Kluwer Medknow Publications, 2016)
Objectives: To evaluate the potential benefit, in terms of pain relief, of the paracervical block with 2% lignocaine in women undergoing hysterosalpingography (HSG). Study Design: This study was a prospective randomized controlled study. Settings: This study was conducted in infertility clinic of a tertiary care center. Materials and Methods: Four hundred and six patients undergoing HSG as a part of infertility evaluation were included in the study. These women were randomized into two groups: Group I received paracervical block with 2% lignocaine at the time of HSG (n = 53) and Group II (n = 53) served as control. Hyoscine (10 mg) oral tablet was given to all the patients 30 min before the procedure. Pain perception during the procedure was analyzed by the patient between 0 and 10 on a numeric rating scale, immediately after HSG. Results: The baseline demographic characteristics of participants in two groups were similar. Mean pain score immediately after HSG in the study group and control group was 4.84 ± 2.56 and 5.21 ± 1.89, respectively (P = 0.21). Conclusions : There is no benefit of paracervical block with 2% lignocaine, in terms of pain relief, in women undergoing HSG.